A correção de rumos de uma nação: a Rússia sob o comando de Vladimir Putin - Sperancete, Luiz Fernando Mocelin (2016)
This work has as objective contribute to the study of the Russian Federation during the long period in which Vladimir Putin is in the Kremlin’s command (2000-2016), and analyze the main aspects of the correction of direction that the Russian leader has been promoting on the political, economic and social course of the country. To this end, references are made to the selected theoretical aspects from “political realism”, having as key-authors Hans Morgenthau, Kenneth Waltz and Nicolau Maquiavel, and to the aspects of historical and social of the Russian’s national identity formation after the 1917’s October Revolution